Qualitative Research on the Training Experiences and Needs of Intensive Care Unit General Nurses Against the Background of Regular Coronavirus Disease 2019 Prevention and Control - Zhang, Yu; Wang, Yan-li; Wang, Shu-qin; Zhang, Chun-yan; Wan, Na; Jia, Yan-rui; Gao, Feng-li (Frontiers in Public Health, 2022)
Objective: This study aimed to investigate the training experiences and needs of intensive care unit (ICU) general nurses against a background of regular Coronavirus disease (COVID-19) prevention and control. Methods: Using the phenomenological method of qualitative research, semi-structured interviews were conducted with 10 ICU nurses. The interview data were analyzed, sorted, summarized, and refined using the content analysis method. Results: The following five themes were extracted from the interviews, based on the training experiences of the nurses: 1) broadening their thinking; 2) discovering their personal shortcomings; 3) gaining self-confidence; 4) calmly facing frontline work; 5) experiencing high assessment pressure. The training needs of the nurses could be summarized into the following four themes: 1) increased training time; 2) improving the assessment mechanism; 3) establishing a normal rotating-shift training system; 4) balancing the teaching levels. Conclusion: Against a background of regular epidemic prevention and control, ICU training for general nurses is of high practical significance and value. Thus, active exploration and research should be conducted to establish perfect training and assessment mechanisms for these nurses. Additionally, training methods that are suitable for clinical needs should be formulated and training systematization and standardization must be promoted.